GEOMETRIC AND PAVEMENT DESIGN EVALUATION OF JAKARTA - CIKAMPEK II SELATAN TOLL ROAD (STA 18+400 - STA 31+200) - Al Imran, Farhan
With increasingly dense population growth and increasingly advanced societal development, the movement of goods and services will also increase, which must then be balanced with improvements in transportation facilities and infrastructure, including the addition of the road network. Toll roads are a type of road that is currently being developed and built massively in Indonesia. Currently the construction of the Jakarta - Cikampek II South Toll Road is being carried out, so the design process for the Jakarta - Cikampek II South Toll Road has been completed according to the regulations in force at that time. The regulations that apply and have become the standard in designing toll road geometry previously were Bina Marga Regulation no. 007/BM/2009. Currently there are new regulations that apply regarding road geometry design, namely Bina Marga Regulation no. 13/P/BM/2021. So it is necessary to evaluate the existing design of the road in accordance with the provisions of the new regulations. In addition, there is potential for optimizing toll road geometric designs to obtain cheaper construction costs. The Jakarta – Cikampek II Selatan Toll Road, which was designed in this Final Project, is 13.1 km long. In the geometric design of the Jakarta – Cikampek II South Toll Road, a 6/2 D configuration is used with a design speed of 80 km/hour. The horizontal bends are designed as 15 PI with 4 SCS bends and 11 FC bends. The vertical bends are designed as 21 PVI with 9 convex curves and 12 concave curves. In road pavement design, for rigid pavement, use the Reinforced Continuous Cement Concrete rigid pavement type. The thickness of the concrete slab used is 305 mm, the thin concrete layer is 100 mm thick, the drainage layer is 150 mm thick. For rigid hardening, asphalt is designed with a granular layer consisting of a 40 mm thick AC – WC layer, a 60 cm thick AC – BC layer, a 75 mm thick AC – Base layer and a class A aggregate foundation layer 300 mm thick. Based on the results of project scheduling, rigid pavement construction took 569 days, while flexible pavement took 582 days. In terms of cost, rigid pavement costs IDR 6,546,833,170,973, while flexible pavement costs IDR 6,990,917,253,156.